PENGEMBANGAN MEDIA PEMBELAJARAN KARTU KUARTET BERBASIS APLIKASI CANVA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS IV SD - Manalu, Eka Widawati; Gandamana, Apiek; Simanjuntak, Eva Betty; Halimatussakdiah, Dr.; Afriadi, Putra (Universitas Negeri Medan, 2024)
This research is motivated by the problem of limited learning media, which causes difficulties for students in understanding the material during the learning process. This study aims to determine the feasibility, practicality, and effectiveness of Canva application-based quartet card learning media for the Pancasila Education subject in Grade IV at SD Negeri 060872, Medan Perjuangan District. This type of research is developmental research (Research and Development) with the 4-D model, consisting of four stages: define, design, development, and disseminate. The subjects of this study were 21 students from Grade IV at SDN 060872, Medan Perjuangan District. Data collection techniques used in the research were interviews, questionnaires, tests, and documentation. This research and development resulted in a product of Canva application-based quartet cards for the Pancasila Education subject in Grade IV at SD Negeri 060872, Medan Perjuangan District. The data analysis techniques used in this study were qualitative and quantitative. The research results show that 1). The feasibility test was categorized as